Diagnostic test accuracy of life-threatening electrocardiographic findings (ST-elevation myocardial infarction equivalents) for acute coronary syndrome after out-of-hospital cardiac arrest without ST-segment elevation. (March 2023) - Yoshimura, Satoshi; Kiguchi, Takeyuki; Irisawa, Taro; Yamada, Tomoki; Yoshiya, Kazuhisa; Park, Changhwi; Nishimura, Tetsuro; Ishibe, Takuya; Kobata, Hitoshi; Kishimoto, Masafumi; Kim, Sung-Ho; Ito, Yusuke; et al.
Abstract: Aim: Life-threatening electrocardiographic (ECG) findings aid in the diagnosis of acute coronary syndrome (ACS), which has not been well-evaluated in patients with out-of-hospital cardiac arrest (OHCA). This study aimed to evaluate the diagnostic test accuracy (DTA) of ST-elevation myocardial infarction (STEMI) equivalents following the return of spontaneous circulation (ROSC) in patients with OHCA to identify patients with ACS. Methods: Using the database of the Comprehensive Registry of In-Hospital Intensive Care for OHCA Survival study from 2012 to 2017, patients aged ≥18 years with non-traumatic OHCA and ventricular fibrillation or pulseless ventricular tachycardia on the arrival of emergency medical service personnel or arrival at the emergency department, who achieved ROSC, were included. Patients without ST-segment elevation or complete left bundle branch block on ECG and those who did not undergo ECG or coronary angiography, were excluded from the study. We evaluated the DTA of STEMI equivalents for the diagnosis of ACS: isolated T-wave inversion, ST-segment depression, Wellens' signs, and ST-segment elevation in lead aVR. Results: Isolated T-wave inversion and Wellens' signs had high specificity for ACS with 0.95 (95% confidence interval [CI], 0.87–0.99) and 0.92 (95% CI, 0.82–0.97), respectively, but their positive likelihood ratios were low, with a wide range of 95% CI: 1.89 (95% CI, 0.51–7.02) and 0.81 (95% CI, 0.25–2.68), respectively. Conclusion: The DTA of STEMI equivalents for the diagnosis of ACS was low among patients with OHCA. Further investigation considering the measurement timing of the ECG after ROSC is required.